Existence Dualism in Kant and its Cartesian Roots - Laiho Hemmo; Koistinen Olli (Centro de Lógica, Epistemologia e História da Ciência (CLE), 2025)
We argue that Kant advocates existence dualism in a largely Cartesian vein. In such a dualism,there are two basic kinds of existence or ways of being: I-existence and categorial existence. I-existence denotes myexistence,whilecategorial existence denotes, basically,the existence of ordinary things. First, we show how the route to existence is fundamentally different in the two cases. Then we ask whether they also indicate two ontologically distinct kindsand argue that I-existence should be regarded as thefundamental kindof existence in any case. One important consequence of this is that I-existence stands outside the Kantian conditions of experience, being the oneun-Copernican element left intact after Kant’s Copernican turn.